Suicidal ideation and attempted suicide among cancer patients during the COVID‐19 pandemic. Issue 12 (29th August 2022) - Ma, Zikun; Mao, Yize; Wang, Yuanyuan; Duan, Zhizhou; Qu, Diyang; Li, Chaofeng; Chen, Runsen; Liu, Zhuowei
Abstract: This study aimed to understand the suicidal ideation and suicidal attempts among cancer patients during the COVID‐19 pandemic. The data were collected from patients diagnosed with cancer while attending the largest cancer center in the south of China. A structured questionnaire was used to investigate patients' demographic data, suicidal behavior, and factors related to COVID‐19. Mental health conditions were measured by the Generalized Anxiety Disorder‐7, the Patient Health Questionnaire‐9, and the Brief Symptom Inventory. Comorbidities and medical conditions of cancer patients were extracted from the electronic healthcare records. Among the 5670 cancer patients, 755 (13.3%) reported suicidal ideation, and 266 (4.7%) reported suicidal attempts during the COVID‐19 pandemic. The age group with the highest risk of suicidal ideation was 20–24 years (23.9%). Lifetime history of suffering from mental disorders, longer time since cancer diagnosis, regional and distant tumor stage, depression, anxiety, hostility, having a higher frequency of worrying about cancer management due to COVID‐19, higher frequency feeling of overwhelming psychological pressure due to COVID‐19, having a higher level of barriers to manage cancer due to COVID‐19, and higher barriers to continue treatment of cancer due to inconveniences caused by COVID‐19, were all significantly associated with increased risk of suicidal ideation. We also identified the risk factors of suicide attempts. This is the first study investigating the prevalence and risk factors associated with suicidal ideation and suicidal attempts in Chinese cancer patients during the COVID‐19 pandemic. Our findings suggest that it is essential to monitor the mental health conditions of this vulnerable population, especially for cancer patients who have comorbidity with a history of mental disorders. Also, government policymakers should take action to protect cancer patients to avoid any interruption of their continued treatment. Further efforts are urgently required to develop specific psychological interventions to reduce the risk factors among cancer patients during the COVID‐19 pandemic.